Psychological Trauma of Ralph in William Golding’s The Lord of the Flies: A Carl Jung Analysis - Eriska Yani Safitri; Otong Setiawan Djuharie (INDO PUBLISHING, 2025)
This study analyzes the psychological trauma experienced by Ralph in Lord of the Flies by William Golding through Gustav Jung’s literary psychology. It focuses on how trauma shapes Ralph’s character development using Jungian concepts: shadow, individuation, and collective unconscious. The research applies a qualitative descriptive method. The main source is the novel itself, supported by literature on trauma theory and Jungian psychology. Data is collected through literature review and text analysis. The analysis uses Jung’s theory to interpret Ralph’s psychological journey. Findings show that Ralph’s trauma is linked to violence, loss, and destruction, which affect his growth. The shadow concept reveals Ralph’s inner conflict between savage instincts and his effort to stay civilized. His individuation emerges as he faces internal darkness, especially when mourning Piggy and witnessing the island’s ruin. The study concludes that trauma significantly influences personal identity and group dynamics. It also highlights the relevance of psychological analysis in literature